Abdominal computed tomography radiation dose for six hospitals at northern region in Malaysia / Izza Nadia Mohd Maulana - Mohd Maulana, Izza Nadia (2015)
Computed tomography (CT) is an advanced imaging modalities. Its powerful ability to assist more precise diagnosis cause it to be used widely in several countries. The risk of radiation to human health has always become a concern among researchers including Malaysia. This is due to the fact that the number of CT scanner and CT procedure in Malaysia is increasing more than 15% from 2009 to 2010. Therefore, it is expected that the number will increase year by year. The aim of this research is to study the variation of radiation dose (dose descriptors) to the patients at the hospitals involved in this research. However, this research is only focus in certain hospitals in northern region of Malaysia. The dose descriptors include weighted CT Dose Index (CTDIw), volume CT dose index (CTDIvol), dose-length product (DLP) and effective dose (E). The data had been collected by using questionnaire distributed to the hospitals. The data was analysed by using CT Expo v 1.4 in order to calculate the dose descriptors. The result showed that there are variation of dose descriptors in all hospitals and the overall result is higher than previous studies. It is hoped that every hospital can implement the guideline recommended by established bodies in order to reduce the radiation dose to the patient.